Konstruksi Jendela Baja Balai Kota Malang - Sujudwijono, Nurachmad; Purwono, Edi Hari; Sugiarto, Totok (RUAS, 2013)
Steel material is a material that has been famous since ancient times, where the material is mostly used when the classical architecture, generally in office buildings. Today the application of steel for the frame and window profiles are rarely encountered, generally used for steel structural system in the form of columns, beams and roof of the building. This is because steel is not resistant to rust, so the cost of treatment is difficult and expensive. This study aims to determine the connection technique steel windows in Malang City Hall building, knowing the advantages of steel as a window grille at Malang City Hall building. The method used is descriptive method, the method of data analysis which includes critical analysis of normative and comparative analysis. The results of the study is expected to be a source of learning in lectures related to the structure and construction of buildings.Keywords: window, steel, Malang City Hall